The Muslim Society in Japan: Their Interaction with the Japanese Society - Yuki, Ahmad Shiozaki (KATHA- The Official Journal of the Centre for Civilisational Dialogue, 2018)
In the contemporary world, for the Japanese, chances to communicate with the Muslims are increasing day by day. Many Muslims stay in Japan as students, workers, and tourists. A part of them become permanent residents in Japan. At the same time, visiting Muslims countries for business and other purposes is not so special experience among the Japanese today. In Japan the encounter between the Japanese and the Muslims resulted in some issues, which are needed to be resolved. Among those issues, there are socio-economic problems such as labor environment, income, and crimes by Muslims who came to Japan. There are problems concerning international marriage between the Japanese and the Muslims, for example, education for children, domestic violence, and divorce. The language as medium in daily life and working place is still big issue for foreigner Muslims. Majority of them are far from fluent in speaking, reading and writing Japanese.